2018
DOI: 10.1002/hyp.11483
|View full text |Cite
|
Sign up to set email alerts
|

Hillslope water tracks in the High Arctic: Seasonal flow dynamics with changing water sources in preferential flow paths

Abstract: Preferential subsurface flow paths known as water tracks are often the principal hydrological pathways of headwater catchments in permafrost areas, exerting an influence on slope physical and biogeochemical processes. In polar deserts, where water resources depend on snow redistribution, water tracks are mostly found in hydrologically active areas downslope from snowdrifts. Here, we measured the flow through seeping water track networks and at the front of a perennial snowdrift, at Ward Hunt Island in the Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 69 publications
4
28
0
Order By: Relevance
“…In this case study, the road alignment is primarily perpendicular to the local hydraulic gradient ( Figure 1b), but subsurface water flow is also possible subparallel to the road embankment. Further, the macroscopic heterogeneity and anisotropy of the subsurface can also control the direction of water flow (e.g., Mackay, 1983;Paquette et al, 2017;Paquette, Fortier, & Vincent, 2018).…”
Section: Thermal Impact Of Subsurface Water Flowmentioning
confidence: 99%
“…In this case study, the road alignment is primarily perpendicular to the local hydraulic gradient ( Figure 1b), but subsurface water flow is also possible subparallel to the road embankment. Further, the macroscopic heterogeneity and anisotropy of the subsurface can also control the direction of water flow (e.g., Mackay, 1983;Paquette et al, 2017;Paquette, Fortier, & Vincent, 2018).…”
Section: Thermal Impact Of Subsurface Water Flowmentioning
confidence: 99%
“…Beneath the active layer, continuous permafrost acts as a barrier that impedes deeper subsurface flow (Ge et al, 2011;Walvoord et al, 2012). Conditions in water tracks differ significantly from those in their nontrack hillslope watersheds and are characterized by a deeper active layer depth, smaller amplitude of annual soil temperature change, coarser subsurface materials (Figure 1b), thicker snowpack, and higher soil moisture and nutrient contents (Ball & Levy, 2015;Curasi et al, 2016;Harms et al, 2019;Hastings et al, 1989;McNamara et al, 1999;Paquette et al, 2018;Rushlow, 2018). Since water tracks have a higher soil moisture content and are closer to their storage capacity than are the adjacent hillslopes, it has been suggested that water tracks are one of the main source areas for runoff to downslope rivers in response to summer rainfall (McNamara et al, 1997;Rushlow & Godsey, 2017) and spring snowmelt (Paquette et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Conditions in water tracks differ significantly from those in their nontrack hillslope watersheds and are characterized by a deeper active layer depth, smaller amplitude of annual soil temperature change, coarser subsurface materials (Figure 1b), thicker snowpack, and higher soil moisture and nutrient contents (Ball & Levy, 2015;Curasi et al, 2016;Harms et al, 2019;Hastings et al, 1989;McNamara et al, 1999;Paquette et al, 2018;Rushlow, 2018). Since water tracks have a higher soil moisture content and are closer to their storage capacity than are the adjacent hillslopes, it has been suggested that water tracks are one of the main source areas for runoff to downslope rivers in response to summer rainfall (McNamara et al, 1997;Rushlow & Godsey, 2017) and spring snowmelt (Paquette et al, 2018). Higher liquid-water saturation in water track soils is also linked to increased solute transport (Levy et al, 2011), nutrient and carbon cycling (Ball & Levy, 2015;Cheng et al, 1998;Harms & Ludwig, 2016;McNamara et al, 2008;Oberbauer et al, 1991;, vegetation productivity (Curasi et al, 2016), and heat transfer (Gooseff et al, 2013;Hastings et al, 1989;Paquette et al, 2016Paquette et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is evident that there are significant differences in the spatial LST distribution under different topographies, especially under different slope aspects. Paquette, Fortier, and Vincent () reported that a combination of steep topography and slope aspect can play a similar role to sunset in the energy balance at polar latitude. Carey and Woo (, , ) reported that different slope aspects exhibit large water flux variabilities as topography, microclimate, soil, frost, and vegetation vary.…”
Section: Introductionmentioning
confidence: 99%